The highway to establishing a commercial information retrieval system. - Lodder M (Electronic Library)
The CSIR's Division of Information Services has developed a sophisticated information access and retrieval system from which it will be able to provide various of its range of information services. The paper describes the road which was followed in order to establish this system. A brief outline is given of the system's three main components, these being a retrieval, a client record management and a communications access component. The system is primarily mainframe-based and runs on the ADABAS database management platform. This is followed by a description of aspects of the management of the development of this system. Mechanisms had to be put in place to ensure that the development work done was in line with the business requirements of the Division. Effective means of ensuring sufficient communication with the many different participants in the project -- including line management, contractors and consultants, operators of the computing facilities and systems development staff -- had to be found. Procedures were put in place to schedule and monitor the many and varied tasks involved in the project. The project also led to the development of a macro-level model of the Division's activities. This model is being developed in increasing levels of detail to provide for the highly integrated nature of the Division's activities and hence of its systems. Lessons learnt in the project, problems experienced and achievements are described.